Intramolecular cyclization assisted oxidative addition: synthesis of octahedral cycloplatinated methyl complexes1. Issue 26 (22nd March 2015) - Shankar, D.; Jaipal, K.; Sridhar, B.; Chary, R. Nagarjuna; Prabhakar, S.; Giribabu, L.; Likhar, Pravin R.
<x xml:space="preserve">Abstract</x> Cycloplatination of XMeC6H4CCC-(Rf) (N-4-OCH3C6H4) [X = S, Se and Rf = perfluoroalkyl groups] with PtCl2 gave a monomeric octahedral Pt(iv) complex. Emission and reactivity studies of the Pt(iv) complexes are discussed.